Generation and propagation of polarization singularities in second harmonic generation from the surface of the isotropic gyrotropic medium - Grigoriev, K.S.; Makarov, V.A.; Perezhogin, I.A.; Portavkin, N.N. (ALT Proceedings, 2026)
When proceeding to the oblique incidence from thenormal incidence geometry in surface secondharmonic generation, the symmetry of the problemand, thus, of the reflected signal beam breaks. Inthis case there can appear C-points in thetransversal section of the signal beam. Using theanalytical formulae obtained in previous works, westudied the conditions of appearance and thebehaviour of the C-points in reflected signal beam(in particular case of SHG), and also the way of theline-to-point singularity transformation.